2021
DOI: 10.2298/tsci200608004k
|View full text |Cite
|
Sign up to set email alerts
|

Global solar radiation prediction model with random forest algorithm

Abstract: Global solar radiation estimation is crucial for regional climate assessment and crop growth. Therefore, studies on the prediction of solar radiation are emerging. With the availability of the public data on solar radiation, computerized models have been developed as well. These Predictive Models play significant role in determining the potentials of regions suitable for renewable energy generation required by engineering and agricultural activities. Herein a computerized model has been prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the application, data are randomly extracted from the dataset D to form a new training set, the training set is subjected to classification regression, and the final output is obtained after weighted calculation and arithmetic average calculation [18]. The dataset of the decision tree can be effectively enhanced by this step, and the generalization ability is improved.…”
Section: Skill Evaluation Model Based On Stochastic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the application, data are randomly extracted from the dataset D to form a new training set, the training set is subjected to classification regression, and the final output is obtained after weighted calculation and arithmetic average calculation [18]. The dataset of the decision tree can be effectively enhanced by this step, and the generalization ability is improved.…”
Section: Skill Evaluation Model Based On Stochastic Algorithmmentioning
confidence: 99%
“…When N takes an infinite value and P takes a value of 0.368, 37% of the data in the training set will not be drawn, and this part of the sample is represented by OOB, a metric that can be used to analyze the error and can also respond to the importance [18]. Based on the submodel of the randomized algorithm when there is the CART model, the Gini index is used as a splitting metric when the decision tree nodes are split to generate a bifurcated decision tree, and each division divides the sample into two subsets.…”
Section: Skill Evaluation Model Based On Stochastic Algorithmmentioning
confidence: 99%
“…The regional estimation of solar radiation has shifted from measurements using expensive and highly maintained instruments to model calculations ( 13 , 14 ). Various empirical models, for example, sunshine-based models ( 15 18 ) and temperature-based models ( 19 21 ) are commonly used due to their simple operation and low computational costs ( 22 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Karasu and Altan proposed a high-performance recognition model for solar radiation based on RF with a feature selection approach to cope with nonlinear dynamics in time series. Kör utilized the RF algorithm to estimate global solar radiation, and results showed that the RF model performed well with a predictive value of 93.9% and determination coefficient ( R 2 ) above 0.938. Generally, RF is effective for solving multivariate nonlinear problems and can be used for downscaling large-scale atmospheric variables and predicting SRI; however, the RF method has difficulties in quantifying the main and interactive effects of climate variables on the SRI …”
Section: Introductionmentioning
confidence: 99%